FAKTOR HUKUM DAN NON HUKUM DALAM PUTUSAN TINDAK PIDANA KORUPSI DI INDONESIA - Ginting, Jamin (Jurnal Media Hukum, 2012)
The role of a judge is very important in deciding corruption cases in Indonesia, if a judge is affected by external which will make him/her unobjective in deciding a corruption case, thus his/her independency is judged. According to the research results, there is difference between cases which occurred in Java Island and Sumatera Island, where there is more corruption cases in Java compared to Sumatera and the punishment is more severe than in Sumatera, apart from that there are a lot of corruption done by company leaders with the average age of 46-54 years old. This shows that a leader of the mentioned range of age tends to misuse their position and opportunities while on the other hand, judges seldom give maximum punishment to corruptorKey words: Corruption, Judged, Independency, Legal Factor, Non Legal Factor.